THE MEDICOLEGAL ASPECT OF CRIMINAL VACCINES AND THEIR CONSEQUENTIAL DAMAGES - Yovita Arie Mangesti (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Healthy human resources will make it easier for the country to achieve development goals in the field of health The development of health sector in Indonesia currently has double burden, namely the burden of infectious diseases and degenerative diseases. For the prevention of infectious diseases, an immunization program is held in Hospitals, clinics, and physician practices. Programs that are good enough to improve public health status are tainted with the circulation of fake vaccines that are not only a medical problem, but also bring implications to the social and legal fields. The existing regulation has not explicitly set forth the forgery of the vaccine, so in law enforcement it is still based on the interpretation of law enforcers both in determining the material law and the formal law of this medicolegal case. It is worth reviewing the role of the law as a means of social control and social engineering. Through a conceptual approach, legislation and hermeneutics, and based on the humanitarian paradigm, this paper seeks to explore the medicolegal aspect of a fake vaccine holistically, so that law as a public guide in health can provide protection for all stakeholders involved mainly in the production, distribution and Use of the vaccine in medical care. Case studies of fake medicolegal vaccine found that during this time, the handling of fake vaccines has not been specifically regulated and still equated with counterfeit medicines, whereas in terms of substance, the vaccine is different from the drugs. Expectations for the creation of responsive legal protection in the field of medical services in the future, strived by reconstruction of the Health Act, a one-door management system, effectiveness and efficiency of government performance, revitalization of professional association functions and law in terms of socialization, health promotion, education, and advocacy.